Effect of HIV infection in the micronuclei frequency on the oral mucosa - Lima, Celina Faig; Alves, Monica Ghislaine Oliveira; Furtado, Juvencio Jose Duailibe; Marcucci, Marcelo; Balducci, Ivan [UNESP]; Almeida, Janete Dias [UNESP] (Wiley, 2017)
Background: The genotoxic impact of HIV infection on the oral cavity malignancies is unknown. The aim of this study was to evaluate the effect of HIV infection in micronucleus (MN) frequency on the oral mucosa of HIV+ patients and establish a relationship with early cytogenetic changes in oral carcinogenesis. Methods: Thirty HIV+ individuals who are under highly active antiretroviral therapy (HAART) and 30 non-HIV patients were evaluated. Two smears were taken from the lateral border of the tongue and mouth floor and stained by Feulgen. The frequency of MN was examined in 3000 cells per subject under common microscopy. Results: MN analysis showed no significant difference between groups by Mann–Whitney U-test for total MNs (P = 0.178). The presence of single MN was greater in control group with statistical significance (P = 0.009), while in HIV group, multiple MNs were exhibited in higher mean. Conclusions: HIV patients under HAART therapy and low viral load values showed higher frequency of multiple MNs, which, although not statistically significant, may be caused by the action of the Vpr gene, an accessory gene of HIV. These results corroborate the theory of HIV infection cytogenetic damage.
Keywords: AIDS; cytodiagnosis; exfoliative cytology; HIV; HIV infection; micronuclei; oral mucosa